Targeting the critical source areas of phosphorus based on hydrological sensitive area delineation to control nonpoint source pollution in watersheds - Zhou, Yiwen; Deng, Jun; Li, Zhaoxia; Wang, Tianwei; Du, Yingni; Zhao, Sijie; Zhang, Xuanming (Frontiers in Environmental Science, 2022)
To pursue higher agricultural output, farmers have invested heavily in fertilizers, pesticides and other factors of production, which inevitably causes agricultural nonpoint source pollution (ANPSP) and seriously restricted the sustainable development of global agriculture. Accurate and efficient integrated prevention and control of ANPSP requires scientific identification of critical source areas and influencing factors of nonpoint source pollution, which is particularly important in geographic conditions where steep-slope agriculture dominates and landscape features are complex. In this study, a typical small watershed in the mountainous area of the Three Gorges Reservoir area was selected, and the risk of nonpoint source phosphorus loss in the watershed was assessed using the Phosphorus Index (PI) on the basis of Soil Topographic Index (STI) prediction of runoff production area in the watershed. Finally, the critical source areas (CSAs) for its loss were identified. The results showed that the area of hydrologically sensitive areas in the watershed was approximately 22.87% of the total study area, with an area of 37.05 hm2. The hydrology of variable source areas within hydrologically sensitive areas plays a dominant role and is more likely to produce runoff and increase the risk of agricultural nonpoint source phosphorus pollution. The results of PI analysis showed that the risk of phosphorus loss was low in most areas of the watershed (45.77%), the areas at high risk of phosphorus loss accounted for 29.33% of the entire watershed with an area of 47.52 hm2, and tea plantation was the most dominant land use type. The critical source area of nonpoint source phosphorus output accounts for 5.47% of the watershed area and is mainly distributed along the watershed system, 82.55% of which is tea plantation. Compared with the traditional phosphorus index evaluation system, this method is important for the accurate identification of critical source areas of nonpoint source pollutants, for strengthening the efficient prevention, control and management of ANPSP, and for improving the utilization rate of arable land as well as land management and sustainable development of watersheds.